Sarcopenia in patients with diabetes mellitus - Dionyssiotis, Yannis; Athanassiou, Panagiotis; Papathanasiou, Jannis; Efstathopoulos, Efstathios; Prokopidis, Konstantinos; Trovas, Georgios; Kostoglou-Athanassiou, Ifigenia (Folia Medica, 2022)
Introduction: Diseases such as diabetes mellitus may be associated with adverse changes in body composition. Sarcopenia is characterized by a progressive and generalized loss of skeletal muscle mass and functionality. Aim: To investigate the relationship between type 2 diabetes mellitus (T2DM) and sarcopenia. Materials and methods: In a retrospective, non-randomized study, 35 T2DM patients, aged 20-80 years, were assessed for sarcopenia prevalence compared to controls (n=16). Appendicular skeletal mass (ASM) (kg) was measured, and sarcopenia was defined as SMI <7.0 and <5.7 kg/m2, in males and females, respectively, using the European Working Group on Sarcopenia in Elderly (EWGOSP) definition. Low physical performance was defined as a walking speed of <0.8 m/s. Results: Incidence of sarcopenia was significantly higher in T2DM patients vs. controls (27% vs. 20%, p=0.01) and elderly vs. young participants (40% vs. 12%, p<0.001), respectively. Walking velocity was significantly lower in T2DM patients compared to male and female controls (1.08±0.22 vs. 1.23±0.18 and 1.07±0.26 vs. 1.26±0.16, respectively, p<0.001,). Conclusions: A moderate prevalence of sarcopenia in patients with type 2 diabetes mellitus was observed, which appeared to increase significantly in older men. Finally, incidence of T2DM displayed decreased physical performance in both genders.